The role of financial performance in mediating the effect of debt restructuring on firm value - Mutty Claudia Dewinda; Mandasari R Mandasari R (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This study aims to analyze the effect of debt restructuring on firm value with financial performance (ROA and ROE) as mediating variables. Design/methodology/approach – This study aims to analyze the effect of debt restructuring on firm value with financial performance (ROA and ROE) as mediating variables. This study employs robust regression analysis in Stata 17 to test the direct and indirect effects of debt restructuring on firm value, with financial performance (ROA and ROE) as mediating variables. Findings – The results show that debt restructuring does not have a significant impact on company value. However, debt restructuring has a significant positive effect on financial performance (ROA) and a significant negative effect on financial performance (ROE). Financial performance also does not have a significant impact on company value and does not mediate the relationship between debt restructuring and company value. Research limitations – The study's limitations include the model's limited ability to explain financial performance and the limited number of variables used. Implications – Debt restructuring needs to be supported by strong strategies and robust information to send a positive signal, and further research is recommended to include additional relevant variables and control variables. Originality – This study contributes to the literature by investigating financial performance (ROA and ROE) as a mediating mechanism between debt restructuring and firm value. The results show that improvements in profitability do not translate into higher firm value, suggesting that restructuring signals are not effectively perceived by the market.